„Trudne” wiersze. Wokół lingwistycznej poezji kobiet - Grądziel-Wójcik, Joanna (Przestrzenie Teorii, 2019)
The article addresses the problem of absence of women’s poetry in the linguistic current of 20th-century Polish poetry. It analyses its causes, amongst which the pivotal role is played by the stereotypical vision of women’s poetry, deeply ingrained in general awareness. The vision in question does not admit “difficult” forms and thus places women’s poetic work outside the avant-garde tendencies, linguistic experiment and metareflection. The authoress calls for inclusion of the omitted or forgotten poetesses who play with language in their poems and she articulates the need to redefine our understanding of linguistic poetry.